Psychological Well-Being For College Students in Ma’had Al-Musawwa Surakarta - Monika Dedisera Monika; Nisa Windiya Hastuti; Abdurrohman Al Khusaini; khasana khasana; Salsabila Kurnia Damayanti (Institut Agama Islam Negeri Jember, 2022)
Anxiety, stress, depression, and various psychological symptoms are now severe problems that stalk students. Moreover, students who live in ma'had or their ma’had are required to divide their time and thoughts and manage themselves well. This study aims to determine the general description of students' psychological well-being in ma’had Al-Musawwa, Surakarta. This study uses a quantitative descriptive approach to collect observation data and questionnaire surveys. The subjects in this study were 25 students who took additional tahfidz classes at the ma’had Al-Musawwa, Surakarta. The results showed that the students of ma’had Al-Musawwa Surakarta have good psychological well-being in self-acceptance, 72%, relationships with others, personal growth, and life goals. And students at ma’had Al-Musawwa Surakarta have low/low psychological well-being in the aspect of environmental control and autonomy with a percentage of 48% and 52%, and a general description of the condition of psychological well-being is exceptionally good or in the moderate category, namely 56% of the total sample.